N036 The advanced nursing care in IBD: Study on biosimilar drugs. (16th January 2018) - Onidi, F M; Simbula, S; Vacca, V; Binaghi, L; Pellecchia, M; Cabras, F; Demurtas, M; Mocci, G
Abstract: Background: inflammatory bowel diseases (IBD) affect in Italy about 200000 patients, with a growing impact on public spending and social care. The use of anti-TNF biologic therapy has improved the outcome of these diseases, however, given the high cost of these therapies, it's necessary to identify strategies to ensure the sustainability of spending. In this scenario, biosimilars play an important role. The aim of this study were to evaluate the savings in expenditure with the introduction of Biosimilar drug, and adherence of patients to the therapy after the nursing counceling. Methods: All dispensations of infliximab were analysed from 01/11/2015 up to 30/04/2017. Patients were considered as "naive" if the therapy with infliximab was started directly with the Biosimilar drug, while "switch" if patients had started the medicine originator and switched to Biosimilar at a later stage. All patients treated with the Biosimilar, naive or switch, received from a nurse of the Centre a general information on the use of the drug. Results: From November 2015 to April 2017 the total number of patients treated with infliximab was 73, of which 34 (47%) for ulcerative colitis (UC) and 39 (53%) for Crohn's disease (CD). The Biosimilar was administered in 28 patients (38.4% of the total), 21 naive (75%) and 7 switch (25%). Among them, 13 patients (46%) were UC and 15 (54%) CD. During the semester from November 1, 2015 to April 30, 2016, 91 vials of biosimilar drug (15% of total infliximab) were dispensed; in the second semester from May 1, 2016 to the October 31, 2016, and in the third semester from November 1, 2016 to April 30, 2017, 149 (22%) and 244 (35%) vials were dispensed, respectively. The savings were €17210.19; €28179.33 and €46146.01, respectively, in the three periods for a total of €91535.53 in a year and a half. All patients treated with Biosimilar drug have allowed for treatment. Conclusions: This study has shown the progressive prescriptions of the infliximab for the treatment of IBD at our hospital. There has been a steady increase in the prescription of Biosimilar drug product, both in naive patients and in patients who had initially taken the originator drug. The outcome of the research was made possible thanks to the collaboration of different professional figures such as pharmacists, gastroenterologists, and specialist clinical nurses in IBD.